2009
DOI: 10.4161/auto.5.3.7724
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in spinal cord injury

Abstract: Previous studies have indicated that autophagy has an important function, not only in many neurodegenerative diseases, but also in traumatic and ischemic brain injury. However, no study has previously shown the contribution of autophagy to neural tissue damage after spinal cord injury. We recently investigated the alterations in Beclin 1 expression and the involvement of autophagy and autophagic cell death after spinal cord injury using a spinal cord hemisection model in mice. The results showed that the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…This upregulation of G-CSF promotes autophagy in SCI Y Guo et al LC3B may maximize and prolong autophagy activity in neurons after treatment with G-CSF. Interestingly, we also find that most nuclei of LC3B-positive cells that are TUNEL positive are round and not shrunken or fragmented, suggesting that in at least some of these injured neurons autophagy may have an important protective role by inhibiting apoptosis at this early stage of SCI, a conclusion supported by Kanno et al 7 The role of autophagy activation during SCI remains a matter of debate. Many investigators regard autophagy as exerting a cytoprotective function that involves a mechanism for recycling injured cells and reducing damage against cell death.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This upregulation of G-CSF promotes autophagy in SCI Y Guo et al LC3B may maximize and prolong autophagy activity in neurons after treatment with G-CSF. Interestingly, we also find that most nuclei of LC3B-positive cells that are TUNEL positive are round and not shrunken or fragmented, suggesting that in at least some of these injured neurons autophagy may have an important protective role by inhibiting apoptosis at this early stage of SCI, a conclusion supported by Kanno et al 7 The role of autophagy activation during SCI remains a matter of debate. Many investigators regard autophagy as exerting a cytoprotective function that involves a mechanism for recycling injured cells and reducing damage against cell death.…”
Section: Discussionsupporting
confidence: 71%
“…4,5 In addition to apoptosis, recent findings have revealed that autophagy represents another mechanism involved with regulating programmed cell death after SCI. 6,7 Autophagy has an important role in the degradation of cytoplasmic constituents via the autophagosomal-lysosomal pathway. 8,9 This pathway provides a means through which damaged organelles, toxic agents and long-lived, unwanted proteins are degraded and recycled, thereby maintaining cellular homeostasis.…”
mentioning
confidence: 99%
“…However, pyknosis may be observed as a result of various cell death pathways (Burgoyne 1999). This realization prompted us to explore alternative processes for delayed death since we have recently observed that cells die even several hours after washout of kainate (Mazzone et al 2010) even if, in the field of spinal cord injury research, a common view is that the early cell death is predominantly by necrosis followed by apoptosis (Liu et al 1997;Baptiste and Fehlings 2006) that can be caspase-dependent (Liu et al 2002;Yu et al 2009) and caspase-independent (Eliasson et al 1997;Mandir et al 2000;Verdaguer et al 2002;Won et al 2002;Yuan et al 2003;Cho and Toledo-Pereyra 2008;Kanno et al 2009). Recently, an alternative cell death pathway, termed parthanatos, involving hyperactivity of poly(ADPribose) polymerase-1 (PARP-1) has been considered important to spinal cord injury (Scott et al 1999;Genovese et al 2005;Wu et al 2009) because it would strongly impair the mitochondrial energy stores.…”
Section: Introductionmentioning
confidence: 97%
“…26,27 Activation of autophagy started at 4 hours post-SCI, peaked at 3 days, and lasted for 21 days. The LC3-positive cells were located in neurons, astrocytes, and oligodendrocytes.…”
mentioning
confidence: 99%